Spherical nanocrystalline barium zirconate titanate prepared by Co-precipitation in highly basic aqueous solution - Panpailin Seeharaj (2018)
Spherical monosized barium zirconate titanate nanoparticles (Ba(ZrxTi1-x)O3(BZT) when x = 0.25, 0.30 and 0.35) have been prepared by co-precipitation in a strongly alkaline solution (20 M NaOH) at 80°C. The phase formation of the as-precipitated powders was characterized by XRD, FT-IR and Raman spectroscopy as a single-phase BZT with cubic perovskite oxide structure. This indicates that crystalline BZT powders can be obtained from the co-precipitation in 20 M NaOH without the requirement of calcination process. SEM analysis showed that BZT had nanosized spherical morphology with uniform shape and size. The crystal sizes obtained by TEM analysis were 20-40 nm. © 2013 Copyright Taylor and Francis Group, LLC.